Viral immunogenicity determines epidemiological fitness in a cohort of DENV-1 infection in Brazil - Pinheiro, Tauyne Menegaldo; Mota, Mânlio Tasso de Oliveira; Watanabe, Aripuanã Sakurada Aranha; Biselli-Périco, Joice Matos; Drumond, Betânia Paiva; Ribeiro, Milene Rocha; Vedovello, Danila; Araújo, Jr., João Pessoa; Pimenta, Paulo Filemon Paolucci; Chaves, Bárbara Aparecida; Silva, Mayara Marques Carneiro da; Batista, Izabella Cristina Andrade; et al. (PLOS Neglected Tropical Diseases, 2018)
The dynamics of dengue virus (DENV) circulation depends on serotype, genotype and lineage replacement and turnover. In São José do Rio Preto, Brazil, we observed that the L6 lineage of DENV-1 (genotype V) remained the dominant circulating lineage even after the introduction of the L1 lineage. We investigated viral fitness and immunogenicity of the L1 and L6 lineages and which factors interfered with the dynamics of DENV epidemics. The results showed a more efficient replicative fitness of L1 over L6 in mosquitoes and in human and non-human primate cell lines. Infections by the L6 lineage were associated with reduced antigenicity, weak B and T cell stimulation and weak host immune system interactions, which were associated with higher viremia. Our data, therefore, demonstrate that reduced viral immunogenicity and consequent greater viremia determined the increased epidemiological fitness of DENV-1 L6 lineage in São José do Rio Preto.